KHAN'S LECTURER : Handbook of the Physics of Radiation Therapy - Khan, Faiz M., author; Mihailidis, Dimitris, contributors; Hassaan Alkhatib, contributors (Philadelphia, PA : Wolters Kluwer and bLippincott Williams & Wilkins, 2011)
PSZJBL